A Life-Cycle Model of Habitual Dependence in Leisure Demand - GURDGIEV, CONSTANTIN (My University, 2008)
This model proposes an extension of the traditional habits in consumption literature to encompass the time-persistence of leisure demand. The model establishes a link between the habitual leisure and income effects, which amplifies the traditional effects on savings, investment and consumption distribution across periods. The disutility of habits stock varies with the strength of habit formation. At the same time, the wage elasticity of demand for leisure and the income elasticity of consumption are shown to be functions of the strength of habit formation. The model concludes that while habitual leisure captures the effects of persistence in leisure, it fails to reflect the time dependency properties of consumption. This warrants a new approach to modelling consumption and leisure demand that includes the possibility for time dependent and weakly inseparable consumption and leisure.
PUBLISHED
Keywords: Economics; Consumption; Leisure; Labor Supply